Peran Guru Pendidikan Agama Islam Dalam Mengembangkan Kematangan Emosional Siswa Sekolah Menengah Pertama Di Masa Pandemi - Ummah Karimah; Ayuhan; Ariq Fadillah Rahman; Mochamad Daffa Akmal; Wanto Hermawan; Muhammad Chairul Banin; Rachmad Daniel (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to (1) determine the role of teachers in developing students' emotional maturity through programs conducted by PAI teachers. (2) knowing the learning strategies for students to remain emotionally mature. (3) knowing the methods applied by PAI teachers. This research use desciptive qualitative approach. The subjects of this study were PAI subject teachers and junior high school students. The method of data collection in this research is interviews. Data analysis carried out in this study used data reduction steps, data presentation, and conclusions. The results of the study found that the PAI teacher at Al Wisdom Islamic Junior High School had a program to help students who were experiencing grief. As for the learning strategy for students to remain emotionally mature, the teacher creates a pleasant learning atmosphere in the classroom. PAI teachers also have methods in developing students' emotional maturity by holding discussions with students